Strategising the Trofical Fruit Farm (MTFF) to be number one agro tourism must visit location in Melaka / Sahuri Musa, Safinaz Sulaiman and Zurairah Jais - Musa, Sahuri; Sulaiman, Safinaz; Jais, Zurairah (Faculty of Business and Management, 2007)
The purpose of this business research is to study the agro-tourism industry in Melaka in which we choose Melaka Tropical Fruit Farm (MTFF) located at Sungai Udang to explore this field. This study looks at viability studies, potential management risks, pricing mechanism and considers the best recommendation to MTFF so that they can attract more visitors in the future. The findings show that MTFF should do the repackaging the package of the SBU and do some market development on the existing product or penetration on some activities in order to satisfied visitors need and wants and to make sure that MTFF will generate profit in the five to ten years duration in the future. Finally, the change model tools are recommended so that MTFF management will change the model of management planning, financial controlling and so on so forth to make sure they implement what are we recommended to them.